Hermeneutic Method Applied to the Antiphona ad Introitum Texts in the 1970 Roman Missal: A Liturgical Inquiry - Christianus Watu (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2026)
The main focus of this research is to propose a hermeneutic method for the texts of the Antiphona ad Introitum (Entrance Antiphon) contained in the Roman Missal of Paul VI (1970) and to apply it to two texts from Dominica II in Quadragesima. The aim of this study is to demonstrate that, through this method, the theological meaning of the text can be thoroughly understood, thereby enabling the faithful to grasp the spiritual fruits contained therein. The conclusion reveals that the theological significance of an antiphon text is profoundly rich, thus requiring a hermeneutic method to help uncover these meanings. Naturally, the hermeneutic method proposed here does not claim to be the only suitable approach for interpreting the entrance antiphon, as the choice of method depends on the specific questions the interpreter intends to address; different questions require different methods. Accordingly, the study employs a literature review conducted with a historical and liturgical hermeneutic perspective.